ICT-based judging support system for artistic gymnastics and intended new world created through 3D sensing technology - Sasaki, K.; Masui, S.; Tezuka, K. (Fujitsu scientific & technical journal, 2018)
The elderly is estimated to make up almost a third of the Japanese population by 2020. Led by the Japan Sports Agency, one of the ministries and agencies related to sports in Japan, initiatives have been launched to make sports one of the country's major industries in collaboration with the healthcare and health promotion fields. Given that the sports business is a big industry overseas, the Japanese government aims to grow the sports market to 15 trillion yen by 2025. 3D sensing technology is drawing attention in the sports IoT area, which is considered important for this market expansion. Fujitsu is pursuing the development of 3D sensing technology to build a judging support system in collaboration with the International Gymnastics Federation and Japan Gymnastics Association. This paper describes the value and new world to be created through Fujitsu's 3D sensing technology, and our efforts to standardize it internationally.